PERAN NOTARIS DALAM PEMBAGIAN WARISAN KEPADA ANAK HASIL LUAR KAWIN DITINJAU DARI HUKUM HARTA KEKAYAAN DAN PEWARISAN SERTA HUKUM WARIS BARAT - Muhammad Sidiq; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The research of this thesis in order to (1) to know the definition of a child outside marriage in a positive law of Indonesia is a child born in a legal marriage according to a religion that fulfills the provisions, it is just not recorded in the civil record; Judging by the Compilation of Islamic Law and the Civil Code (2) to know the magnitude of division of marriage out of the Compilation of Islamic Law and Civil Code (3) to know there is a Notary's role in the division of inheritance in the making of Statement of Inheritance and Certificate of Inheritance. Starting a dispute relating to the building of a married child in the future, the Notary may make peace deeds and / or agreements on the release of copyright.This research uses normative juridical approach. This study uses secondary legal materials, which include positive laws or regulations, research results, scientific papers, and other legal literature references that support problem analysis. This approach seeks to examine and explore and seek answers to what should be of every problem.This study produces in essence (1) Outsider is a child born in a legal marriage according to religion is not yet recorded. Therefore, according to Islam, the outsider is legally and legally entitled to inheritance, as well as seen from the perspective of civil law (2) The magnitude of the division of marriage out of the Compilation of Islamic Law is to use the calculations commonly used to divide the inheritance Using principles in KHI. Similarly, the Civil Code that divides the inheritance of children outside of marriage based on the principle of the Civil Code. In contrast to the inheritance division of an out-of-wedlock child (in the sense of the Civil Code) divided according to which group he was abandoned. The offspring studied by the authors differ from the definition of children outside marriage in the Civil Code (3) The role of a notary in the division of inheritance contributes to the making of the Statement of Inheritance and the Inheritance Certificate. In the event of a dispute, a Notary may produce peace deeds and / or an agreement of waiver of claim.Keywords: Outsider married, Marriage Law, Compilation of Islamic Law, Notary